Pelatihan Pencegahan dan Penanganan/Pengendalian Bahaya Kebakaran untuk Masyarakat Lingkungan Kampus Institut Teknologi dan Logistik Trisakti - Wahyudono Wahyudono; Supri Supri; Surya Tri Saputra; Nawang Kalbuana; Dhian Supardam; Alwajir Abdusshomad; Oke Hendra; Rahmawati Sukra (Politeknik Penerbangan Indonesia Curug, 2026)
Fire incidents may occur suddenly, including residential areas, workplaces, and public spaces. Understanding fire characteristics, potential ignition sources, and appropriate fire handling and extinguishing methods is essential, as improper actions may increase risks and worsen emergency situations. For instance, using water to extinguish fires caused by oil or electrical sources can result in more severe hazards. This community training program was conducted to enhance public capacity and awareness in managing fire risks in residential and workplace environments. The program aimed to strengthen participants’ theoretical understanding and practical skills related to fire prevention and initial fire response. The implementation methods included educational sessions, demonstrations, and direct hands-on fire extinguishing practices conducted both manually and using portable fire extinguishers (APAR). The purpose of this activity are expected to increase community awareness of the importance of safety culture, reduce the number of fire incidents, and improve community preparedness in fire prevention and initial response. Ultimately, participants are expected to be able to respond quickly, appropriately, and safely during emergency situations.